2009
DOI: 10.1007/s12177-009-9044-4
|View full text |Cite
|
Sign up to set email alerts
|

Ocular disease in patients with ANCA-positive vasculitis

Abstract: Anti-neutrophil cytoplasmic antibody (ANCA)-positive vasculitis—the term recently applied to Wegener's granulomatosis—is a rare multi-system inflammation characterized by necrotizing granulomas and vasculitis. We investigated the ocular manifestations of this disease in a group of patients drawn from five inflammatory eye disease clinics across the United States. Of 8,562 persons with ocular inflammation, 59 individuals were diagnosed with ANCA-positive vasculitis; 35 males and 21 females, aged 16 to 96 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 26 publications
0
46
0
2
Order By: Relevance
“…However, uveitis as a secondary phenomenon to scleritis, termed sclerouveitis, is more commonly encountered [10, 24]. Anterior uveitis is the most common sequela of scleritis, and in particular, necrotizing scleritis [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, uveitis as a secondary phenomenon to scleritis, termed sclerouveitis, is more commonly encountered [10, 24]. Anterior uveitis is the most common sequela of scleritis, and in particular, necrotizing scleritis [23].…”
Section: Discussionmentioning
confidence: 99%
“…According to a large cohort study of antineutrophil cytoplasmic antibody (ANCA)-positive patients, GPA-associated uveitis can involve one or both eyes, and can affect any anatomical region of the eye, with anterior uveitis being the most common [10]. The study also reported co-occurring scleritis in 50% of the patients with anterior uveitis, suggesting that uveitis presents as a secondary phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…These findings differ from our previous series, where the proportions were 14% for diffuse anterior and 78% for necrotising scleritis in patients with GPA,2 but are in agreement with those reported in other series. Hoang et al 23 found that 71% had diffuse anterior scleritis, Watkins et al 22 described that 47.6% of patients showed diffuse anterior and 28% showed necrotising scleritis and Gu et al 19 reported that 86% of their patients suffered a necrotising disease. Again, the observed difference could be due to the low prevalence of the disease; this also likely explains why in this current series we did not find patients with associated posterior scleritis, while other series described a prevalence of 3.6% and 14%, as well as single case reports of posterior scleritis as the initial manifestation of PR3-ANCA-associated vasculitis 22–24.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, scleritis is a hallmark of Wegener's granulomatosis (19). Watkins et al reported on 59 ANCA-positive patients with ocular inflammations, which included scleritis (75%), uveitis (17.9%), and other ocular inflammatory conditions (33.9%) such as peripheral ulcerative keratitis and orbital pseudotumor (20). …”
Section: Discussionmentioning
confidence: 99%